Novel yeast isolated from broilers feedstuff, gut and faeces as aflatoxin 1 B1 adsorbents - Magnoli, Alejandra Paola; Rodriguez Romera, Mariela Carmen; Poloni, V.L.; Combina, Mariana; Chiacchiera, Sebastián; Dalcero, Ana María; Cavaglieri, Lilia Reneé; Rojo, María Cecilia (2017)
Aims: To isolate and characterize native yeast strains from broilers’ environment as feedstuff, faeces and gut, and to evaluate their binding capacity for aflatoxin B1 (AFB1). Methods and Results: A total of nine yeast strains were isolated: three from feedstuff identified as Pichia kudriavzevii (2) and Clavispora lusitaniae (1), two from gut identified as Candida tropicalis and four from faeces identified as Cl. lusitaniae (3) and Cyberlindnera fabianii (1). AFB1 binding percentages varied among yeast strains and with AFB1 concentrations. To carry out adsorption studies, one strain from each genus and each origin was selected as follows: Cl. lusitaniae and P. kudriavzevii from feedstuff, Cl. lusitaniae and Cy. fabianii from faeces and Ca. tropicalis from gut. The most appropriate concentrations for cells and toxin were 107 cells per ml and 100 ng ml _1 of AFB1 respectively. All the tested yeast strains showed similar adsorption capacities independently of the origin. The adsorption isotherm studies in all yeasts assayed showed behaviour of L type or Langmuir and a varied affinity for the toxin. The stability of the AFB1–yeast complex demonstrated the irreversibility of the binding process. Conclusion: Yeast strains tested in this study constitute potential AFB1 adsorbents and they possess the advantage to be native from the avian environment. Significance and Impact of the Study: This study makes a contribution to using native yeasts from broilers’ environment for controlling chronic aflatoxicosis in avian production.